Education Without Walls: The Promise of Virtual Labs in the Teaching Process - Simanca H, Fredys A.; Palacios, Jairo; Barbosa, Lugo Manuel; Quintero, Cristian Duney Bermúdez (Journal of Ecohumanism, 2024)
Virtual labs are digital spaces that overcome the physical limitations of traditional classrooms. They employ simulation to foster real-time collaboration. Through these virtual platforms, the ways students address and understand theoretical concepts are transformed. In addition to concepts and principles, virtual labs help students develop fundamental professional skills, such as problem solving, application design, and error detection. Therefore, this study conducted a literature review to analyze virtual labs’ potential to offer an education that is more accessible, dynamic, and interactive by foreseeing major changes in teaching processes. Virtual labs were found to represent a necessary and promising revolution within the field of higher education. Their implementation reflects not only the process of adaptation to a world undergoing constant technological changes but also the current and future needs of a varied and globalized student population.